2007
DOI: 10.1242/jcs.015834
|View full text |Cite
|
Sign up to set email alerts
|

The increase of cell-membranous phosphatidylcholines containing polyunsaturated fatty acid residues induces phosphorylation of p53 through activation of ATR

Abstract: The G1 phase of the cell cycle is marked by the rapid turnover of phospholipids. This turnover is regulated by CTP:phosphocholine-cytidylyltransferase (CCT) and group VIA Ca2+-independent-phospholipase A2 (iPLA2). We previously reported that inhibition of iPLA2 arrests cells in G1 phase of the cell cycle by activating the p53-p21 checkpoint. Here we further characterize the mechanism of p53 activation. We show that specific inhibition of iPLA2 induces a time dependent phosphorylation of Ser15 in p53 in the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 63 publications
(78 reference statements)
4
38
0
1
Order By: Relevance
“…The ability of iPLA 2 ␤ to promote cell proliferation becomes prominent in the context of tumorigenesis. Several in vitro studies reveal higher expression of iPLA 2 ␤ in stimulated immortal cell lines and that chemical inhibition or siRNAs targeted against iPLA 2 ␤ reduces proliferation and promotes apoptosis of the cells ( 97, 108,125,[356][357][358][359][360][361][362][363][364]. Subsequent studies targeting specifi c cancers suggest that iPLA 2 ␤ promotes cancer cell growth via signal transduction pathways involving epidermal growth factor receptors, MAPKs, E3 ubiquitin-protein ligase mdm2, tumor suppressor protein p53, and cell cycle regulator p21 (365)(366)(367).…”
Section: Ipla 2 ␤ and Diseasesmentioning
confidence: 99%
“…The ability of iPLA 2 ␤ to promote cell proliferation becomes prominent in the context of tumorigenesis. Several in vitro studies reveal higher expression of iPLA 2 ␤ in stimulated immortal cell lines and that chemical inhibition or siRNAs targeted against iPLA 2 ␤ reduces proliferation and promotes apoptosis of the cells ( 97, 108,125,[356][357][358][359][360][361][362][363][364]. Subsequent studies targeting specifi c cancers suggest that iPLA 2 ␤ promotes cancer cell growth via signal transduction pathways involving epidermal growth factor receptors, MAPKs, E3 ubiquitin-protein ligase mdm2, tumor suppressor protein p53, and cell cycle regulator p21 (365)(366)(367).…”
Section: Ipla 2 ␤ and Diseasesmentioning
confidence: 99%
“…With respect to cell cycle regulation, some researchers have reported that cell cycle arrest was closely associated with metabolic events in plasma membranes [21,22,[26][27][28][29]. We have previously reported that HL affects the fluidity of plasma membranes [30], cellular lipid constituents [31][32][33][34][35][36][37] and lipid microdomain (lipid rafts [30] or caveolae structures [31]) in cancer cells, and trigger the growth-inhibition or apoptosis. Although the mechanistic details are not yet clear, it seems that HL could accumulate in plasma membranes of NSCLC cells [13], change the membrane characteristics related to cell cycle progression, and induce G 0 /G 1 phase arrest or apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…The data do not exclude a connection between irradiation and an induced turnover of phospholipids that influence cell signaling. It is known that PUFA levels in membrane lipids correlate with p53 levels [29,30] and also that gamma irradiation is connected with p53 induction and the apoptotic response. However, to date, no systematic research has been performed on membrane lipid remodelling due to irradiation conditions and the related membrane signalling.…”
Section: Effect Of In Vivo Obt Exposure and In Vitromentioning
confidence: 99%